A laboratory calibration of a model Helly-Smith bedload sampler / Azmi Abu Kassim - Abu Kassim, Azmi (1991)
It is a common knowledge that water flowing in natural or artificial channels often has the ability to scour sand, gravel or even large boulders from the bed or banks and sweep them downstream. This phenomenon is usually termed as "sediment transport" and the sediment that has been transported by rolling on or near the streambed is termed as "bedload". While various types of different samplers such as Arnhem and Helley - Smith bed load sampler have been developed and many theoretical approaches through mathematical means have been put forward it is found that results are frequently disappointing and often far from satisfactory.